Repair of microdamage in osteonal cortical bone adjacent to bone screw. - Lei Wang; Tingjun Ye; Lianfu Deng; Jin Shao; Jin Qi; Qi Zhou; Li Wei; Shijing Qiu (PLoS ONE, 2014)
Up to date, little is known about the repair mode of microdamage in osteonal cortical bone resulting from bone screw implantation. In this study, self-tapping titanium cortical bone screws were inserted into the tibial diaphyses of 24 adult male rabbits. The animals were sacrificed at 1 day, 2 weeks, 1 month and 2 months after surgery. Histomorphometric measurement and confocal microscopy were performed on basic fuchsin stained bone sections to examine the morphological characteristics of microdamage, bone resorption activity and spatial relationship between microdamage and bone resorption. Diffuse and linear cracks were coexisted in peri-screw bone. Intracortical bone resorption was significantly increased 2 weeks after screw installation and reach to the maximum at 1 month. There was no significant difference in bone resorption between 1-month and 2-months groups. Microdamage was significantly decreased within 1 month after surgery. Bone resorption was predisposed to occur in the region of <100 µm from the bone-screw interface, where had extensive diffuse damage mixed with linear cracks. Different patterns of resorption cavities appeared in peri-screw bone. These data suggest that 1) the complex microdamage composed of diffuse damage and linear cracks is a strong stimulator for initiating targeted bone remodeling; 2) bone resorption activities taking place on the surfaces of differently oriented Haversian and Volkmann canals work in a team for the repair of extensive microdamage; 3) targeted bone remodeling is a short-term reaction to microdamage and thereby it may not be able to remove all microdamage resulting from bone screw insertion.